1937
DOI: 10.1037/h0062207
|View full text |Cite
|
Sign up to set email alerts
|

A study of instability using the Goodenough drawing scale.

Abstract: I N practically every phase of the study and interpretation of maladjustment, psychologists and psychiatrists differ. It appears that the basic reason for these controversies lies in the fact that the study, observations, and description of maladjustment have been largely literary in type and subjective in nature. One finds, therefore, a variety of opinions and generalizations that can be easily discarded on the ground that they have never been subjected to a rigorous experimental study.The failure of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1940
1940
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is interesting to note that the pattern of the differences is the same as that found by those who have compared normal and retarded children; this in spite of the fact that the two groups were equated for total score on the drawing test. Berrien's (33) study, discussed later in this paper, attempts an item analysis to obtain a diagnostic measure of different types of behavior disorder in children, The possibility of using the Draw-a-Man Test as an indicator of maladjustment was also studied by Brill (41), who found that his maladjusted boys typically scored lower on this scale than they did on the Binet while the reverse was more often true of the well-adjusted. His attempt to devise a short form of the drawing test for the purpose of predicting maladjustment commits the too-familiar statistical error of using the same data for validating as for deriving the scale.…”
Section: Studies In the Psychology Of Children's Drawings 387 •mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the pattern of the differences is the same as that found by those who have compared normal and retarded children; this in spite of the fact that the two groups were equated for total score on the drawing test. Berrien's (33) study, discussed later in this paper, attempts an item analysis to obtain a diagnostic measure of different types of behavior disorder in children, The possibility of using the Draw-a-Man Test as an indicator of maladjustment was also studied by Brill (41), who found that his maladjusted boys typically scored lower on this scale than they did on the Binet while the reverse was more often true of the well-adjusted. His attempt to devise a short form of the drawing test for the purpose of predicting maladjustment commits the too-familiar statistical error of using the same data for validating as for deriving the scale.…”
Section: Studies In the Psychology Of Children's Drawings 387 •mentioning
confidence: 99%
“…Whorley (pp. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], after a careful analysis of the literature on the subject, decided that the elements of compositional unity upon which authorities seemed best agreed are three in number, viz. ; emphasis, balance, and fitness.…”
Section: Studies In the Psychology Of Children's Drawings 387 •mentioning
confidence: 99%
“…Brill (5) has attempted to use the Goodenough Drawing scale as a means of studying instability, selecting nine elements of the scale which may "prove diagnostic of adjustment." He found four items showing conclusive differences between the adjusted and maladjusted, and five showing a probability of reliable difference.…”
Section: Brief Summary Of Other Investigationsmentioning
confidence: 99%
“…Drawing, art work, and construction with plastic materials may give children an excellent opportunity to work out their aggressions harmlessly. Much that would otherwise be inexplicable in their behavior is sometimes thus revealed (i, 5, 10,17,48,67). At Bellevue Hospital in New York City, interesting work is being done in the Children's Ward by the use of puppets (6).…”
Section: Other Diagnostic Aidsmentioning
confidence: 99%